EFFECT OF COWANIN ON CYCLIN D1 EXPRESSION IN MCF-7/HER2 BREAST CANCER CELLS - HEFNI, DIRA; DACHRIYANUS; NAHDA, ANGELICA MAYSYA; WAHYUNI, FATMA SRI (International Journal of Applied Pharmaceutics, 2024)
Objective: Cowanin, isolated from the stem bark of Asam kandis (Garcinia cowa Roxb.) has been known to have cytotoxic activity in MCF-7/HER2 breast cancer cells. Recent studies have reported that cowanin compounds can inhibit MCF-7/HER2 cell migration and the T47D cell cycle in the G0-G1 phase. This research aims to determine the effect of cowanin on the cyclin D1 protein expression in MCF-7/HER2 breast cancer cells. Methods: The treatment consisted of a negative control group and a group given cowanin at a concentration of IC50 value (10,51 µM). The expression of cyclin D1 protein was detected using the western blot method. Observations of protein area and density were carried out using ImageJ software. Data were analyzed using the independent T-test. Results: The research showed that cowanin compounds induced cell cycle arrest of MCF-7/HER2 breast cancer cells by reducing the expression of cyclin D1 protein (p<0,05). Conclusion: The findings show that cowanin can significantly decrease the area and density of cyclin D1 protein